Enhancing Glucose Recovery from Hibiscus cannabinus L. through Phosphoric Acid Pretreatment - Duangporn Premjet; Suwanan Wongleang; Siripong Premjet (Energies, 2022)
Non-food lignocellulosic biomass is an attractive source owing to its abundance as a renewable resource and cost-effectiveness. Hibiscus cannabinus L., commonly known as kenaf, is a fiber-producing plant with high cellulose yield and non-food biomass. This study aimed to enhance the glucose recovery (GR) of kenaf biomass (KB). The bark and core fibers of KB are rich in glucan content and low in lignin content. Based on its glucan and lignin contents, KB has considerable potential as a feedstock for synthesizing monomer sugars, which can produce biofuel and high-value compounds. Therefore, the bark and core fibers were treated at a moderate temperature with various concentrations of phosphoric acid, followed by enzymatic hydrolysis. After pretreatment, the chemical composition of both feedstocks was changed. Phosphoric acid substantially affected the elimination of partial lignin and hemicellulose, which led to enhanced enzymatic hydrolysis. The maximum hydrolysis efficiency (HE) and GR of bark and core fibers were achieved when both feedstocks were treated with 75% phosphoric acid. Compared with untreated feedstocks, HE increased by approximately 5.6 times for bark and 4.7 times for core fibers. However, GR was enhanced approximately 4.9-fold for bark and 4.3-fold for core fibers.